A Scalable System for Generation of Mesenchymal Stem Cells Derived from Induced Pluripotent Cells Employing Bioreactors and Degradable Microcarriers. (10th September 2021) - Rogers, Robert E.; Haskell, Andrew; White, Berkley P.; Dalal, Sujata; Lopez, Megan; Tahan, Daniel; Pan, Simin; Kaur, Gagandeep; Kim, Hyemee; Barreda, Heather; Woodard, Susan L.; Benavides, Oscar R.; et al.
Abstract: Human mesenchymal stem cells (hMSCs) are effective in treating disorders resulting from an inflammatory or heightened immune response. The hMSCs derived from induced pluripotent stem cells (ihMSCs) share the characteristics of tissue derived hMSCs but lack challenges associated with limited tissue sources and donor variation. To meet the expected future demand for ihMSCs, there is a need to develop scalable methods for their production at clinical yields while retaining immunomodulatory efficacy. Herein, we describe a platform for the scalable expansion and rapid harvest of ihMSCs with robust immunomodulatory activity using degradable gelatin methacryloyl (GelMA) microcarriers. GelMA microcarriers were rapidly and reproducibly fabricated using a custom microfluidic step emulsification device at relatively low cost. Using vertical wheel bioreactors, 8.8 to 16.3-fold expansion of ihMSCs was achieved over 8 days. Complete recovery by 5-minute digestion of the microcarriers with standard cell dissociation reagents resulted in >95% viability. The ihMSCs matched or exceeded immunomodulatory potential in vitro when compared with ihMSCs expanded on monolayers. This is the first description of a robust, scalable, and cost-effective method for generation of immunomodulatory ihMSCs, representing a significant contribution to their translational potential. : A scalable system for the generation and rapid harvest of immunomodulatory induced pluripotent stem cell-derived mesenchymal stem cells..